CREATION OF EDUCATIONAL MATERIALS IN THE KEYNOTE FOR TABLET iPAD - LAVRINCIK, Jan (Trends in education, 2013)
Paper deals with the use of tablets Apple iPad in education. The distinctive emphasis mainly on the use of existing electronic training for teachers, it the form of presentation created in PowerPoint primarily. I focus my attention on the mobile version of keynote as a tool for creating presentations and subsequent presentation. At the end, we try to find the contribution of tablets and Apple iPad Keynote in the current education system.
Keywords: Apple iPad; iOS; Keynote; tablet; teaching materials